A REVIEW OF FOSSIL AND RECENT SPECIES OF THE FAMILY ITHYCERIDAE (COLEOPTERA) FROM THE WORLD FAUNA - A. A. Legalov (Амурский зоологический журнал, 2009)
The family review is performed. Eccoptarthrinae, Ulyaninae, Slonikinae and Ithycerinae are united into one family. New tribes Chilecarini Legalov, trib.n. (type genus: Chilecar Kuschel, 1992), Ulyaniscini Legalov, trib.n. (type genus: Ulyanisca Gratshev, 1998) and subtribe Carodesina Legalov, subtrib.n. (type genus: Carodes Zimmermann, 1994) are described. New systematic placements are proposed: tribes Paleocartini Legalov, 2003, placem.n. and Brenthorrhinoidini Legalov, 2003, placem.n. are transfered from family Rhynchitidae to family Ithyceridae; subfamily Slonikinae Zherichin, 1977, placem.n. is transfered from family Nemonychidae to family Ithyceridae; genus Ulyanisca Gratshev, 1998, placem.n. is transfered from subfamily Ulyaninae to subfamily Slonikinae; genus Gratshevibelus Soriano, 2009, placem.n. is transfered from family Belidae to family Ithyceridae; Montsecanomalus rugosithorax (Gratshev & Zherikhin, 2000), placem.n., M. zherichini (Liu & Ren, 2006), placem.n. and M. punctatus (Liu & Ren, 2007), placem.n. are transfered from genus Cretonanophyes Zherikhin, 1977 to genus Montsecanomalus Soriano, Gratshev, Delclòs, 2006. Changes of status: Ulyaninae Zherichin, 1993, stat.n. is downgraded from family to subfamily, Caritae Thompson, 1992, stat.n. and Baissorhynchitae Zherikhin, 1993, stat.n. are downgraded from subfamilies to supertribes, Mesophyletini Poinar, 2006, stat.n. is downgraded from subfamily to tribe, Leptocar Liu & Ren, 2007, stat.n. is downgraded from genus to subgenus, Nebrenthorrhinini Legalov, 2007, stat.n. is upgraded from subtribe to tribe. Four new combinations are proposed: Montsecanomalus rugosithorax (Gratshev & Zherikhin, 2000), comb.n., M. zherichini (Liu & Ren, 2006), comb.n., M. punctatus (Liu & Ren, 2007), comb.n. and M. polychaetus (Liu & Ren, 2007), comb.n.